A low-carbon durable marine cement mortar and its production process
By using low-carbon and environmentally friendly materials such as sulfate cement in offshore cement mortar and optimizing the formulation and process, the performance problems of offshore concrete in extreme marine environments and the high carbon emissions of traditional offshore cement mortars have been solved, and the development of low-carbon and durable offshore cement mortars has been achieved.
Patent Information
- Application Number
- CN202411563455.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The performance of existing offshore concrete protective materials is affected in extreme marine environments, and traditional offshore cement mortar has high carbon emissions and poor environmental protection.
Low-carbon and durable marine cement mortar is used, and its raw materials include sulfur-aluminate cement, modified molecular sieve, standard sand, mineral powder, cellulose ether, corrosion inhibitor, water reducer, surfactant, polyphosphate, inulin and exciter. By optimizing the formulation and process, it improves carbonization, frost resistance and penetration resistance.
The offshore cement mortar with low carbon and environmental protection, high durability and frost resistance has been achieved, reducing carbon emissions and environmental impacts, and extending its service life.
Smart Images

Figure BDA0005118557680000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine engineering concrete protective materials and relates to a low-carbon durable marine engineering cement mortar and a production process thereof. Background Art
[0002] Marine cement mortar plays an important role in marine engineering. It is used to fill and reinforce gaps and cracks in structures such as seabeds, seawalls, and submarine pipelines, ensuring the safety and stable operation of marine engineering structures. The performance of traditional marine cement mortar is poor. In recent years, marine polymer concrete has developed rapidly and gradually replaced traditional marine cement mortar.
[0003] Although the durability of marine polymer concrete is better than that of ordinary concrete, its performance may still be affected to a certain extent in extreme marine environments, such as strong corrosion, high salinity, strong winds and waves. These extreme conditions may accelerate the erosion and aging process of concrete, affecting the safety and service life of the structure; in addition, the environmental protection of marine polymer concrete is also an issue that needs attention. During the production and use process, some harmful substances or waste may be generated, which will have a certain impact on the environment. Therefore, when promoting and applying marine polymer concrete, it is necessary to fully consider its environmental protection and take effective measures to reduce the impact on the environment. In order to better increase the durability of marine polymer concrete, special ingredients such as mineral admixtures and high-performance admixtures are often added to the concrete to improve the performance of the concrete, improve the impermeability and durability, and thus effectively resist the erosion of the marine environment. Currently, the most studied method is to add polymers, such as asphalt modified rubber powder, polyurethane polymers, polyamide polymers, etc., but these polymers will reduce the strength of concrete to a certain extent, and these polymers have poor frost resistance; on the other hand, traditional marine cement mortar has the problem of high carbon emissions. Currently, some low-carbon and environmentally friendly cements and aggregates are used as the main raw materials, such as sulphoaluminate. Although it can greatly reduce carbon emissions and reduce the impact on the environment, its special components lead to reduced frost resistance of marine polymer concrete.
[0004] In general, marine engineering concrete protective materials, especially marine engineering polymer concrete, play an important role in marine engineering construction. Therefore, there is an urgent need for a marine engineering concrete protective material with low carbon, environmental protection, better durability and frost resistance. Summary of the invention
[0005] The purpose of the present invention is to provide a low-carbon durable marine engineering cement mortar and a production process thereof. The marine engineering cement mortar has the advantages of low carbon, environmental protection and high durability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a low-carbon durable marine cement mortar, whose raw materials include, by weight: 20-50 parts of sulphoaluminate cement, 5-30 parts of modified molecular sieve, 100 parts of standard sand, 5-20 parts of mineral powder, 0.05-1 part of cellulose ether, 0.05-0.5 part of corrosion inhibitor, 0.1-1 part of water reducer, 0.1-1 part of surfactant, 0.05-1 part of polyphosphate, 0.5-5 parts of inulin, 0.1-2 parts of activator, and 10-35 parts of water.
[0008] In the present invention, the various raw material components cooperate with each other to make the marine cement mortar have excellent durability.
[0009] In the present invention, in order to further increase the comprehensive performance of marine cement mortar, further, the low-carbon durable marine cement mortar, measured by weight, its raw materials include: 40-45 parts of sulphoaluminate cement, 10-15 parts of modified molecular sieve, 100 parts of standard sand, 8-12 parts of mineral powder, 0.1-0.2 parts of cellulose ether, 0.15-0.2 parts of corrosion inhibitor, 0.2-0.4 parts of water reducer, 0.3-0.5 parts of surfactant, 0.1-0.2 parts of polyphosphate, 1.5-2 parts of inulin, 0.6-0.8 parts of activator, and 20-25 parts of water.
[0010] Sulphoaluminate cement is mainly composed of calcium sulfoaluminate minerals (such as calcium sulphate) and other aluminate minerals, which form a hardened body through hydration reaction. The use of sulfoaluminate cement as the main material in the present invention can form a low-carbon green cementitious material with other raw materials, which can overcome the problem of high carbon emissions of traditional low-carbon green cementitious materials.
[0011] The sulphoaluminate cement in the present invention is a rapid hardening sulphoaluminate cement, codenamed R·SAC.
[0012] The preparation method of the modified molecular sieve comprises: loading the molecular sieve into a fixed bed reactor, and then introducing HF gas for modification to obtain the modified molecular sieve.
[0013] The molecular sieve modified with HF can make the marine cement mortar in the present invention have better anti-carbonation ability. It is speculated that this may be because the marine cement mortar prepared by combining the modified molecules with the components such as mineral powder, standard sand, sulphoaluminate cement and alkali activator in the system can absorb acid ions and further increase the adsorption capacity of carbon dioxide. It itself will not be damaged by acid ions, thereby increasing the anti-carbonation ability of the marine cement mortar.
[0014] Furthermore, the molecular sieve is at least one selected from MCM-11 molecular sieve, MCM-22 molecular sieve, TS-1 titanium silicon molecular sieve and SAPO-18 molecular sieve, preferably MCM-22 molecular sieve.
[0015] The addition of molecular sieves can increase the comprehensive performance of marine cement mortar to a certain extent. After experimental screening, it was found that when MCM-22 molecular sieve is used, marine cement mortar has better anti-carbonation and anti-permeation properties. This may be because the special flaky crystal structure of MCM-22 molecular sieve and its special internal structure can better promote the stability of the slurry-aggregate interface and prevent carbon dioxide and other substances from entering the matrix to a certain extent.
[0016] Furthermore, the average particle size of the molecular sieve is 0.1-100 microns, preferably 1-10 microns.
[0017] Furthermore, the molecular sieve is MCM-22 molecular sieve, and its average particle size is 1-10 microns.
[0018] The MCM-22 molecular sieve in the present invention can be obtained commercially, preferably purchased from Raodong (Liaoning) New Materials Co., Ltd.
[0019] Furthermore, the modification conditions include: a temperature of 200-300°C, preferably 250-280°C; a space velocity of HF gas of 1-5h -1 , preferably 1.5-2h -1 .
[0020] The internal structure of the modified molecular sieve modified under the modification conditions can better adsorb carbon dioxide.
[0021] Standard sand is a specific type of sand used in the construction and engineering fields. After processing, it is quartz sand that meets the standard requirements. Furthermore, the standard sand is at least one of river sand, machine-made sand, sea sand and desert sand with a fineness modulus between 2.3 and 3.
[0022] Furthermore, the mineral powder is S95 grade mineral powder.
[0023] Cellulose ether is a kind of polymer compound with ether structure made of cellulose, which has many excellent properties, such as thickening, good water solubility, suspension or latex stability, protective colloid effect, film-forming property and water retention, etc. Furthermore, the cellulose ether is selected from one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose, preferably hydroxypropyl methyl cellulose.
[0024] The hydroxypropyl methylcellulose in the present invention is at least one selected from hydroxypropyl methylcellulose K100M, hydroxypropyl methylcellulose K100LV, hydroxypropyl methylcellulose K200 and hydroxypropyl methylcellulose K300, preferably hydroxypropyl methylcellulose K200.
[0025] Furthermore, the corrosion inhibitor is selected from at least one of hydroxyethylidene diphosphonic acid, inositol hexaphosphate and tripropylene glycol.
[0026] Furthermore, the corrosion inhibitor is hydroxyethylidene diphosphonic acid and inositol hexaphosphate, and preferably the weight ratio of hydroxyethylidene diphosphonic acid to inositol hexaphosphate is 1:(0.5-2), preferably 1:(1-1.5).
[0027] In the present invention, the synergistic effect of hydroxyethylidene diphosphonic acid and inositol hexaphosphate can better increase the corrosion resistance of marine cement mortar.
[0028] Water reducers are mainly used in concrete construction to reduce the amount of water required to achieve the predetermined concrete workability, strength and durability. It can use less water while maintaining the same fluidity. This can not only improve the strength of concrete, but also improve its durability and construction performance. The water reducer in the present invention can be any water reducer in the art, and further, the water reducer is selected from polycarboxylate water reducer.
[0029] The polycarboxylate water reducer in the present invention can be obtained from the market, such as 530P polycarboxylate water reducer, 325C polycarboxylate water reducer, and SP-409 polycarboxylate water reducer.
[0030] Furthermore, the surfactant is a silicone surfactant and an imidazoline surfactant.
[0031] Furthermore, the weight ratio of the silicone surfactant to the imidazoline surfactant is 1:(0.3-1), preferably 1:(0.5-0.8).
[0032] Furthermore, the silicone surfactant is selected from Evonik TEGOPREN 5840.
[0033] Furthermore, the imidazoline surfactant is selected from 2-dodecyl-N-hydroxyethyl-N-carboxymethyl imidazoline and / or 2-dodecyl-N-hydroxyethyl-N-carboxymethyl imidazoline.
[0034] Furthermore, the polyphosphate is selected from sodium polyphosphate and / or potassium polyphosphate, preferably sodium polyphosphate.
[0035] The polyphosphate in the present invention can be obtained commercially. Preferably, for example, the sodium polyphosphate is purchased from Hubei Huada Fine Chemical Co., Ltd. as sodium tripolyphosphate.
[0036] In the present invention, polyphosphate, silicone surfactant and imidazoline surfactant can better cooperate with each other, can better increase the frost resistance of cement mortar, and the addition of polyphosphate can also increase the corrosion resistance of cement mortar to a certain extent. It is speculated that this may be because the cement mortar system is alkaline as a whole. In this system, the imidazoline surfactant is anionic and has better foaming and water-reducing effects. On the one hand, polyphosphate can chelate with some cations, and on the other hand, it can interact with silicone surfactants and imidazoline surfactants in cement mortar to produce smaller bubbles, thereby improving the fluidity and frost resistance of concrete. Silicone surfactants have better wettability and can be adsorbed on the inner surface of bubbles to stabilize the existence of bubbles, thereby improving the frost resistance of cement mortar.
[0037] Furthermore, the inulin is selected from at least one of natural inulin, short-chain inulin and long-chain inulin.
[0038] The respective inulins in the present invention can be purchased from corresponding models on the market, for example, the models of natural inulin include Orafti natural inulin GR and cosucra natural inulin Instant, the models of short-chain inulin include Orafti short-chain inulin HIS and cosucra short-chain inulin F97, and the model of long-chain inulin includes Orafti long-chain inulin HP.
[0039] Furthermore, the inulin is short-chain inulin.
[0040] In the present invention, adding inulin, especially short-chain inulin, can better increase the anti-permeability of cement mortar, probably because short-chain inulin has more hydroxyl groups, which can react with the silanol groups on the modified molecular sieve to form a denser and more uniform three-dimensional interpenetrating polymer network structure in the system.
[0041] The activator can react chemically with the mineral components in cement to generate new hydration products, thereby improving the strength of concrete. It can also improve the internal microstructure of concrete and make the interface between cement stone and aggregate more tightly bonded. Furthermore, the activator is selected from sodium silicate and sodium aluminate.
[0042] Furthermore, the weight ratio of sodium silicate to sodium aluminate is 1:(0.5-1.5), preferably 1:(0.8-1.2).
[0043] The second aspect of the present invention provides a production process for low-carbon durable marine cement mortar, the production process comprising:
[0044] (1) mixing sulphoaluminate cement, modified molecular sieve, standard sand and mineral powder to obtain a dry mix;
[0045] (2) mixing water and a water reducing agent, adding the mixture to the dry blend, performing a first stirring, and then adding cellulose ether, a corrosion inhibitor, a surfactant, a polyphosphate, inulin and an activator, performing a second stirring to obtain a mixture;
[0046] (3) The mixture is poured and shaken into shape, and cured at room temperature for a specified age to obtain a low-carbon durable marine cement mortar.
[0047] There is no particular limitation on the mixing described in (1) and (2) of the present invention. It only needs to be mixed uniformly. Those skilled in the art can select the mixing method according to their needs. The present invention will not be described in detail here.
[0048] Furthermore, the first stirring condition is stirring at 100-120 r / min for 90-120 s, and the second stirring condition is stirring at 280-300 r / min for 90-120 s.
[0049] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0050] 1. Low-carbon and environmentally friendly: By selecting low-carbon and environmentally friendly raw materials and optimizing the formula, carbon emissions can be greatly reduced and the impact on the environment can be reduced;
[0051] 2. Improved durability: By adjusting the raw material components and optimizing the formula, the corrosion resistance, erosion resistance and penetration resistance of cement mortar can be improved, and its service life can be extended;
[0052] 3. Comprehensive performance optimization: The low-carbon and durable marine cement mortar of the present invention seeks a balance between low carbon and durability, which can ensure that the cement mortar achieves better performance in terms of environmental protection and performance. DETAILED DESCRIPTION
[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] This embodiment provides a low-carbon durable marine cement mortar:
[0056] The low-carbon durable marine cement mortar comprises, by weight, 42 parts of sulphoaluminate cement, 12 parts of modified molecular sieve, 100 parts of standard sand, 10 parts of mineral powder, 0.15 parts of cellulose ether, 1.18 parts of corrosion inhibitor, 0.3 parts of water reducer, 0.4 parts of surfactant, 0.15 parts of polyphosphate, 1.8 parts of inulin, 0.7 parts of activator and 23 parts of water.
[0057] Sulphoaluminate cement is a fast-hardening sulphoaluminate cement, codenamed R·SAC;
[0058] The preparation method of the modified molecular sieve includes: loading the molecular sieve into a fixed bed reactor, and then introducing HF gas to modify the molecular sieve to obtain the modified molecular sieve; the molecular sieve is MCM-22 molecular sieve, the average particle size of which is 8 microns, purchased from Raodong (Liaoning) New Materials Co., Ltd.; the modification conditions include: the temperature is 265°C; the space velocity of the HF gas is 1.5h -1 ;
[0059] Standard sand is sea sand with an average fineness modulus between 2.8;
[0060] The mineral powder is S95 grade mineral powder;
[0061] The cellulose ether is hydroxypropyl methylcellulose K200;
[0062] The corrosion inhibitor is hydroxyethylidene diphosphonic acid and inositol hexaphosphate, and the weight ratio thereof is 1:1.2;
[0063] The water reducer is a 325C polycarboxylate water reducer.
[0064] The surfactants are silicone surfactants and imidazoline surfactants;
[0065] The weight ratio of the silicone surfactant to the imidazoline surfactant is 1:0.65; the silicone surfactant is selected from Evonik TEGOPREN 5840; the imidazoline surfactant is 2-dodecyl-N-hydroxyethyl-N-carboxymethylimidazoline;
[0066] The polyphosphate was sodium polyphosphate, purchased from Hubei Huada Fine Chemical Co., Ltd. as sodium tripolyphosphate;
[0067] Inulin is Orafti short-chain inulin HIS;
[0068] The activators are sodium silicate and sodium aluminate;
[0069] The weight ratio of sodium silicate to sodium aluminate is 1:1;
[0070] The production process of low-carbon durable marine cement mortar comprises: (1) mixing sulphoaluminate cement, modified molecular sieve, standard sand and mineral powder to obtain a dry mixture; (2) mixing water and a water reducer and adding the mixture to the dry mixture for a first stirring, and then adding cellulose ether, a corrosion inhibitor, a surfactant, polyphosphate, inulin and an activator for a second stirring to obtain a mixture; (3) pouring and shaking the mixture to form it, and curing it at room temperature for a specified age to obtain a low-carbon durable marine cement mortar.
[0071] The first stirring condition was stirring at 100 r / min for 100 s, and the second stirring condition was stirring at 300 r / min for 100 s.
[0072] Example 2
[0073] This embodiment provides a low-carbon durable marine cement mortar:
[0074] The low-carbon durable marine cement mortar comprises, by weight, 30 parts of sulphoaluminate cement, 12 parts of modified molecular sieve, 100 parts of standard sand, 5 parts of mineral powder, 0.2 parts of cellulose ether, 0.2 parts of corrosion inhibitor, 0.1 parts of water reducer, 0.1 parts of surfactant, 0.15 parts of polyphosphate, 2 parts of inulin, 0.8 parts of activator, and 20 parts of water.
[0075] Sulphoaluminate cement is a fast-hardening sulphoaluminate cement, codenamed R·SAC;
[0076] The preparation method of the modified molecular sieve includes: loading the molecular sieve into a fixed bed reactor, and then introducing HF gas to modify the molecular sieve to obtain the modified molecular sieve; the molecular sieve is MCM-22 molecular sieve, the average particle size of which is 8 microns, purchased from Raodong (Liaoning) New Materials Co., Ltd.; the modification conditions include: the temperature is 280°C; the space velocity of the HF gas is 1.5h -1 ;
[0077] Standard sand is sea sand with an average fineness modulus between 2.8;
[0078] The mineral powder is S95 grade mineral powder;
[0079] The cellulose ether is hydroxypropyl methylcellulose K200;
[0080] The corrosion inhibitor is hydroxyethylidene diphosphonic acid and inositol hexaphosphate, and the weight ratio thereof is 1:1.5;
[0081] The water reducer is a 325C polycarboxylate water reducer;
[0082] The surfactant is an organosilicon surfactant and an imidazoline surfactant; the weight ratio of the organosilicon surfactant to the imidazoline surfactant is 1:0.5; the organosilicon surfactant is selected from Evonik TEGOPREN 5840; the imidazoline surfactant is 2-dodecyl-N-hydroxyethyl-N-carboxymethyl imidazoline;
[0083] The polyphosphate was sodium polyphosphate, purchased from Hubei Huada Fine Chemical Co., Ltd. as sodium tripolyphosphate;
[0084] Inulin is Orafti short-chain inulin HIS;
[0085] The activators are sodium silicate and sodium aluminate;
[0086] The weight ratio of sodium silicate to sodium aluminate is 1:0.8;
[0087] The production process of low-carbon durable marine cement mortar comprises: (1) mixing sulphoaluminate cement, modified molecular sieve, standard sand and mineral powder to obtain a dry mix; (2) mixing water and a water reducer and adding the mixture to the dry mix for a first stirring, and then adding cellulose ether, a corrosion inhibitor, a surfactant, polyphosphate, inulin and an activator for a second stirring to obtain a mixture; (3) pouring and shaking the mixture to form, and curing the mixture at room temperature for a specified age to obtain a low-carbon durable marine cement mortar;
[0088] The first stirring condition was stirring at 100 r / min for 100 s, and the second stirring condition was stirring at 300 r / min for 100 s.
[0089] Comparative Example 1
[0090] The difference between this comparative example and Example 1 is:
[0091] MCM-22 molecular sieve was used to replace the modified molecular sieve.
[0092] Comparative Example 2
[0093] The difference between this comparative example and Example 1 is:
[0094] The molecular sieve was SAPO-18 molecular sieve with an average particle size of 5 μm, purchased from Raodong (Liaoning) New Materials Co., Ltd.
[0095] Comparative Example 3
[0096] The difference between this comparative example and Example 1 is:
[0097] The modified molecular sieve is 0 parts, that is, no modified molecular sieve is added in the preparation process.
[0098] Comparative Example 4
[0099] The difference between this comparative example and Example 1 is:
[0100] Inulin was Orafti long-chain inulin HP.
[0101] Comparative Example 5
[0102] The difference between this comparative example and Example 1 is:
[0103] The amount of inulin is 0, that is, no inulin is added in the preparation process.
[0104] Comparative Example 6
[0105] The difference between this comparative example and Example 1 is:
[0106] The amount of polyphosphate is 0 parts, that is, no polyphosphate is added in the preparation process.
[0107] Comparative Example 7
[0108] The difference between this comparative example and Example 1 is:
[0109] The surfactant is an imidazoline surfactant.
[0110] Comparative Example 8
[0111] The difference between this comparative example and Example 1 is:
[0112] The surfactant is a silicone surfactant.
[0113] The performance tests were performed on the low-carbon durable marine cement mortars in Examples 1 to 2 and Comparative Examples 1 to 8 respectively:
[0114] 1. Carbonation resistance: Refer to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and test the average carbonation depth of concrete samples after 28 days of standard curing (unit: mm).
[0115] 2. Frost resistance: Refer to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" to measure the dynamic elastic modulus after 200 freeze-thaw cycles. The dynamic elastic modulus is greater than or equal to 95% and is recorded as Grade A, the dynamic elastic modulus is less than 95% and greater than 90%, which is recorded as Grade B, the dynamic elastic modulus is less than 90% and greater than or equal to 85% is recorded as Grade C, and the dynamic elastic modulus is less than 85% as Grade D.
[0116] 3. Water seepage height test: refer to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and test the average water seepage height (unit: mm) of the concrete sample after 28 days of standard curing.
[0117] The test results are shown in Table 1:
[0118] Table 1 Performance test results
[0119]
[0120] It can be seen from the above performance test result table that the carbonization resistance, frost resistance and water permeability of Examples 1 and 2 are the best, especially the comprehensive performance of Example 1 is the most outstanding. This is mainly because the various raw material components cooperate with each other, especially the modified molecular sieve can hinder the entry of carbon dioxide, even if it enters the modified molecular sieve, it can be absorbed and will not be damaged by acid ions itself. Polyphosphates, silicone surfactants and imidazoline surfactants can better cooperate with each other and can better increase the frost resistance of cement mortar. Short-chain inulin has more hydroxyl groups, which can react with the silicon hydroxyl groups on the modified molecular sieve to form a denser, denser and more uniform three-dimensional interpenetrating polymer network structure in the system. However, the comparative examples were significantly inferior to the embodiments in the corresponding performance tests because they did not adopt the necessary technical solutions. In comparative example 1, the molecular sieve was not modified, and it can be seen that the average carbonization depth of the marine cement mortar was significantly increased, and the average permeable water height was slightly increased; in comparative example 2, other types of molecular sieves were used for modification, the carbonization depth was significantly increased, and the average permeable water height was slightly increased; in comparative example 3, no modified molecular sieve was added, the carbonization depth was significantly increased, and the average permeable water height was significantly increased. From the results of comparative examples 1 to 3, it can be seen that the use of specific modification means to modify a specific molecular sieve, any change in the modified molecular sieve obtained by the means has an impact on the carbonation resistance, impermeability and durability of the marine cement mortar; in comparative example 4, the type of inulin was changed to long-chain inulin, the average carbonization depth of the marine cement mortar was slightly increased, and the permeable water height was significantly increased; in comparative example 5, no modified molecular sieve was added With the addition of inulin, the average carbonization depth of the marine cement mortar is significantly increased, and the height of the permeated water is significantly increased. From the results of Comparative Examples 4-5, it can be seen that the use of inulin, especially short-chain inulin, can significantly increase the impermeability of marine cement mortar, and the addition of inulin will also affect the carbonation resistance and frost resistance of marine cement mortar to a certain extent; no polyphosphate is used in Comparative Example 6, and the frost resistance grade of the marine cement mortar is C; in Comparative Example 7, all surfactants are imidazoline surfactants, no silicone surfactants, and the frost resistance grade of the marine cement mortar is C; in Comparative Example 8, all surfactants are silicone surfactants, no imidazoline surfactants, and the frost resistance grade of the marine cement mortar is D; from the results of Comparative Examples 6-8, it is proved that polyphosphates, imidazoline surfactants and silicone surfactants have a synergistic effect in the present invention to increase the frost resistance of marine cement mortar. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
[0121] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low-carbon durable marine cement mortar, characterized in that: The low-carbon durable marine cement mortar comprises, by weight, 20-50 parts of sulphoaluminate cement, 5-30 parts of modified molecular sieve, 100 parts of standard sand, 5-20 parts of mineral powder, 0.05-1 part of cellulose ether, 0.05-0.5 part of corrosion inhibitor, 0.1-1 part of water reducer, 0.1-1 part of surfactant, 0.05-1 part of polyphosphate, 0.5-5 parts of inulin, 0.1-2 parts of activator, and 10-35 parts of water; The preparation method of the modified molecular sieve comprises: loading the molecular sieve into a fixed bed reactor, and then introducing HF gas to modify the molecular sieve to obtain the modified molecular sieve; The molecular sieve is MCM-22 molecular sieve; The surfactant is a silicone surfactant and an imidazoline surfactant, and the weight ratio thereof is 1:(0.3-1); The inulin is short-chain inulin.
2. A low-carbon durable marine cement mortar according to claim 1, characterized in that: The low-carbon durable marine cement mortar comprises, by weight, 40-45 parts of sulphoaluminate cement, 10-15 parts of modified molecular sieve, 100 parts of standard sand, 8-12 parts of mineral powder, 0.1-0.2 parts of cellulose ether, 0.15-0.2 parts of corrosion inhibitor, 0.2-0.4 parts of water reducer, 0.3-0.5 parts of surfactant, 0.1-0.2 parts of polyphosphate, 1.5-2 parts of inulin, 0.6-0.8 parts of activator and 20-25 parts of water.
3. A low-carbon durable marine cement mortar according to claim 2, characterized in that: The modification conditions include: temperature of 200-300°C; HF gas space velocity of 1-5h -1 .
4. A low-carbon durable marine cement mortar according to claim 1 or 2, characterized in that: The cellulose ether is selected from one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.
5. A low-carbon durable marine cement mortar according to claim 1 or 2, characterized in that: The corrosion inhibitor is selected from at least one of hydroxyethylidene diphosphonic acid and inositol hexaphosphate; and the water reducer is selected from polycarboxylic acid water reducer.
6. A low-carbon durable marine cement mortar according to claim 5, characterized in that: The imidazoline surfactant is 2-dodecyl-N-hydroxyethyl-N-carboxymethyl imidazoline.
7. A low-carbon durable marine cement mortar according to claim 1 or 2, characterized in that: The polyphosphate is selected from sodium polyphosphate and / or potassium polyphosphate; the activator is selected from sodium silicate and sodium aluminate.
8. The production process of a low-carbon durable marine cement mortar according to any one of claims 1 to 7, characterized in that: The production process includes: (1) mixing sulphoaluminate cement, modified molecular sieve, standard sand and mineral powder to obtain a dry mix; (2) mixing water and a water reducing agent, adding the mixture to the dry blend, performing a first stirring, and then adding cellulose ether, a corrosion inhibitor, a surfactant, a polyphosphate, inulin, and an activator, performing a second stirring to obtain a mixture; (3) The mixture is poured and shaken into shape, and cured at room temperature for a specified age to obtain a low-carbon durable marine cement mortar.
Citation Information
Patent Citations
Carbon capture concrete based on metal organic framework material and preparation method thereof
CN115626798A
High-toughness and high-durability marine concrete protective coating and preparation method thereof
CN118271883A